OPTIMIZATION OF THE AIRCRAFT ASSIGNMENT MODEL IN THE ALKI II REGION UNDERNEATH THE OPERATION OF SECOND FLEET COMMAND - Mardi Winoelyo; Bambang Ispri; Anton Nugroho (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2022)
Assignment Marine security operation is an operation where the presence at sea has strategic value for theexistence of national sovereignty and maritime security in Indonesia's national jurisdiction. The threat of securitydisturbances and violations at sea in the form of fishing theft, theft of timber and other natural resources as wellas encroachment on territorial boundaries by foreign ships requires the presence of the Indonesian navy PatrolElements (Ships and Aircraft) for security. The limited number of Indonesian navy Patrol Elements and the budgetprovided by the state as well as the need for securing the maritime territory of the Republic of Indonesia haveresulted in the need for thinking about optimizing the assignment of Patrol Ships and Aircraft in the Kamlaoperation sector and placement to their supporting bases, so that the right type and amount and operational costsin security. Ships and aircraft carry out patrols in randomly determined sectors. This optimization model identifiesthe related decision variables through open interview discussions, then sets the objective and constraint functionsas an optimization model to be developed. The application of the Goal Programming method which can beformulated by determining the decision variables related to the assignment of aircraft where the objective functionis to calculate the maximum radar coverage area in the operating sector and minimize operating costs. Meanwhile,Mamdani's Fuzzy Logic method is used to determine the output of certain radar coverage areas. In this case, itrequires the help of Matlab software on the Fuzzy Inference System (FIZ) toolbox to solve this problem.Keywords: “Maritime Patrol Aircraft, Coverage, Operating Costs, Goal Programming, Fuzzy Inference System,and Mamdani Fuzzy Logic”.